Clinical outcomes and risk factors of Acinetobacter baumannii meningitis in pediatric patients at a tertiary hospital in China - Wang, Zixuan; Ye, Lijing; Fu, Pan; Wu, Xia; Xu, Jun; Ye, Yingzi; Han, Shuzhen; Wang, Chuanqing; Yu, Hui (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectivesTo summarize the clinical characteristics, outcomes and identify risk factors of Acinetobacter baumannii (AB) meningitis in children.MethodsThis was a single-center, retrospective study. Children hospitalized between January 2016 and December 2021 who were diagnosed with AB meningitis were included. The clinical characteristics and outcomes were reviewed. Risk factors were determined using univariate analyses (chi-square and Mann-Whitney U tests).ResultsSeventeen patients were included; 15 cases were secondary to neurosurgery, and two were neonates with primary bacterial meningitis. Common symptoms included fever, convulsions and nervous system abnormalities. Cerebrospinal fluid (CSF) tests typically showed increased white blood cell counts dominated by neutrophils, reduced glucose levels and elevated protein levels. Ten patients were successfully treated (successful treatment [ST] group); seven had failed treatment (failed treatment [FT] group). Univariate analyses revealed that mechanical ventilation, routine white cell counts in the peripheral blood, procalcitonin, protein in the CSF, septic shock and carbapenem-resistant AB (CRAB) differed significantly between the groups.ConclusionAB meningitis in children has a high mortality rate. FT was associated with mechanical ventilation, septic shock, CRAB, lower peripheral leukocyte counts, higher protein levels in the CSF and procalcitonin. Larger studies are needed to identify independent risk factors for adverse outcomes.